Freedom of expression cannot be a veil to conceal the abuses practiced by the media - Folena de Oliveira, Jorge Rubem (2013)
This article considers the possibility public power has to regulate and oversee business activities in the social communication segment in Brazil, without having the imposition of the feared censorship, as proclaimed by those who control the information.